2021
DOI: 10.21608/ejhm.2021.175172
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Dexmedetomidine Versus Dexamethasone as Adjuvants to Levobupivacaine for Cervical Plexus Block in Patients Undergoing Thyroid Operation. Prospective-Randomized Clinical Trial

Abstract: Background: Thyroidectomy is the most common endocrine surgical procedure, and many challenges are encountered during the preoperative, intraoperative, and postoperative periods. After thyroidectomy, bilateral superficial cervical block is the most successful option reducing postoperative pain, analgesic needs and postoperative complications such as vomiting. Objective: Our study aimed to evaluate the analgesic effect, onset time of sensory block, duration time, postoperative visual analogue score (VAS) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The mean total analgesic dose of tablet or injection of diclofenac, given in the first 24 hours in both groups, was comparable. It has been similarly observed in studies done by Elbahrawy et al , [ 3 ] Banu et al , [ 4 ] Hassan et al , [ 12 ] and Santosh et al . [ 18 ] that the addition of either dexmedetomidine or dexamethasone as an adjunct to the LA in BSCPB results in a reduction of post-operative analgesic requirement.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The mean total analgesic dose of tablet or injection of diclofenac, given in the first 24 hours in both groups, was comparable. It has been similarly observed in studies done by Elbahrawy et al , [ 3 ] Banu et al , [ 4 ] Hassan et al , [ 12 ] and Santosh et al . [ 18 ] that the addition of either dexmedetomidine or dexamethasone as an adjunct to the LA in BSCPB results in a reduction of post-operative analgesic requirement.…”
Section: Discussionsupporting
confidence: 75%
“…A steady decline in all three parameters was observed in the initial part of intraoperative monitoring in both groups A and B, possibly due to the synergistic effect of drugs used for induction of anaesthesia, namely injection midazolam, fentanyl, propofol, and vecuronium. From 30 minutes to 75 minutes of surgery, there was a statistically significant difference in all SBP, DBP, and HR, with vitals being lower in group A than in group B. Aliste et al , [ 11 ] Hassan et al , [ 12 ] and Albrecht et al . [ 13 ] also reported a similar decrease with dexmedetomidine while comparing it with dexamethasone as an adjuvant for various blocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers had found that addition of dexmedetomidine (50 µg) to 30 ml ropivacaine 0.5% in ultrasound-guided supraclavicular brachial plexus block resulted in earlier onset of sensory block (19) . Also, it was earlier in Hassan et al study with p value 0.007 between dexmedetomidine and dexamethasone as adjuvants to levobupivacaine for cervical plexus block in patients undergoing thyroid operation (20) .…”
Section: Resultsmentioning
confidence: 83%